(untitled) (Journal of Pharmaceutical Negative Results, 2023)
COVID-19 is a disease that can lead to acute respiratory distress syndrome (ARDS). It spread to 200 nations and has been declared a worldwide pandemic by the World Health Organisation (WHO). Until now, there have been more than 237 million positive COVID-19 cases recorded, with around 4.84 million deaths worldwide. General preventive practises such as face masks, hand washing, social distancing, frequent hand sanitising, and other prevention and control (IPC) measures have helped to reduce the risk of getting infected. The aim of this study was to determine the knowledge and attitude towards general prevention of COVID-19 other than vaccination among undergraduate students as prevention is better than cure. Therefore, we believe that this study will give us an opportunity to increase the knowledge as well as to promote their attitude towards general prevention of COVID-19 other than vaccination among undergraduate students. Cross-sectional and convenience sampling method was used throughout the research whereby the responses of 342 undergraduate students with 109 Malays, 159 Chinese and 74 Indians from both medical and non-medical fields were collected through online platforms. The data was analysed by using Statistical Package for the Social Science (SPSS). Based on the data collected regarding comparison of the knowledge between medical and non-medical undergraduate students about general prevention of COVID-19 other than vaccination, questions 6 and 11 were statistically significant with P values less than 0.05 (P < 0.05) while questions 1,2,3,4,5,7,8,9, and 10 showed statistically not significant as their P values were greater than 0.05 (P > 0.05). In addition, for the comparison of attitudes between medical and non-medical towards general prevention of COVID-19 other than vaccination among undergraduate students, questions 1 to 20 were shown statistically not significant as their P values were greater than 0.05 (P > 0.05). Therefore, in conclusion, our study revealed that there was no significant difference between knowledge and attitudes towards the general prevention of COVID-19 other than vaccination among medical and non-medical undergraduate students. The findings obtained from our study may be utilised as an extension for implementing awareness campaigns between the undergraduate students.